Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

L'étude éducation à l'emplois (E2E) - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
Au Québec, la communauté noire et la communauté d'expression anglaise occupent toutes deux des positions relativement précaires sur le plan économique et de l'emploi : toutes deux connaissent des taux de chômage supérieurs à la moyenne et gagnent des revenus médians après impôt inférieurs à ceux de la population totale de la province. La communauté noire d'expression anglaise (CNEA) se trouve à l'intersection de ces deux communautés et subit la double marginalisation d'être à la fois une minorité raciale et linguistique au Québec.

The Education to Employability Study - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
In Québec, both the Black community and the English-speaking community occupy relatively precarious economic and employment positions: both experience higher-thanaverage unemployment rates and earn lower median after-tax incomes compared to the province’s total population. The English-speaking Black Community (ESBC) sits at the intersection of these two communities, and experiences the double marginalization of being both a racial and linguistic minority in Québec.

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

The Black Community Resource Centre Presents : The Infographic Series : Demographics of Quebec's English-speaking Black Population - Black Community Resource Centre (BCRC) (2022)

Croissance de l’opposition à la définition restrictive de la communauté d’expression anglaise - Quebec Community Groups Network (QCGN) (2021)

Opposition Grows to Restrictive Definition of English-speaking Community - Quebec Community Groups Network (QCGN) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Black in Quebec Presents : In Focus - Davids, John; Fang, Xiaoyan (Black Community Resource Centre (BCRC), 2021)
Due to the Information Gaps pertaining to the well-being of the ESBC, the project collected detailed, qualitative information from members of Quebec's ESBC through conducting Focus Groups. These were meant to better inform the project about different aspects of the community such as the challenges facing the ESBC and solutions which should be considered. This process occurred in two parts, one-on-one interviews with members of the ESBC as well as group discussions with members of the seniors in the ESBC. Ultimately, upon conducting the Focus Groups, the Black in Quebec team was provided with a large amount of detailed, qualitative data derived directly from community members. This document presents the findings from the Focus Groups which are organized in two parts: challenges identified and solution based responses. Given that the Focus Group discussions were semistructured and participants offered varying levels of details, the findings reflect distinct issues or solutions identified by the participants in no particular order but were categorized thematically. Certain findings may have overlapped more than one theme.

Quebec's English-speaking Black Community : An Analysis of the Outcomes and Information Gaps - Black Community Resource Centre (BCRC) (2021)
Black in Quebec (BIQ) is a research project being undertaken by the Black Community Resource Center (BCRC), a non-profit organization founded in 1995, which serves Montreal’s English-speaking Black Community (ESBC) by providing individuals with services and information that they need. The BIQ project seeks to answer the Research Question: What is the relative well-being of the English-speaking Black community in Quebec? The relatively unique positioning of the ESBC in the Quebec landscape, being both a visible minority and linguistic minority group, necessitates that research be conducted to further understanding of the experiences and situations facing this community, which are particular to the group or shared more widely across society. The overall vision of this project is to consolidate the collection and dissemination of data that pertains to Quebec’s English-speaking Black community and share this information across a variety of institutions, including Black community organizations, public institutions, and social research groups.

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

2021 Community Vitality Survey : Black in Quebec - Black Community Resource Centre (BCRC) (2021)
This report offers a comprehensive overview of the 2021 Community Vitality Survey which was conducted by the Black in Quebec project team. Black in Quebec was launched in Fall 2019 and was a research project by the Black Community Resource Centre (BCRC) which researched the well-being and vitality of Quebec's English-speaking Black Community (ESBC). This is the third report to be released by the project team and complements the two previous research based publications. The first published report was Quebec's English-speaking Black Community: An Analysis of Outcomes and Information Gaps which was based on an assessment of currently available information pertaining to the English-speaking Black Community in Quebec. The second report to be released was entitled Black in Quebec presents: In Focus and it presented an overview of the Focus Groups conducted by the project team from May to December of 2020. This report focuses exclusively on the 2021 Community Vitality Survey which was conducted from April to June 2021 and provides a detailed overview of the survey. It is the last research based report to be released by the Black in Quebec project before the release of a final, comprehensive project summary report.

Black in Quebec : Summary Report 2020-2021 - Black Community Resource Centre (BCRC) (2021)
In Quebec, there is a population of around 320,000 people who identify as members of the Black community. In Quebec's Black community, just under 60,000 (around 1 in 5 people) are categorized as members of the English-speaking community (Statistics Canada, 2016). The Black in Quebec Project commenced in Fall 2019 with the drafting of the project and in February 2020, the Project Researcher (John Davids) and Research Assistant (Xiaoyan Fang) were hired by the BCRC. The purpose of the project is to fill the gaps in the knowledge about the English-speaking Black Community (ESBC) in Quebec. In Quebec and Canada, there is a lack of disaggregated race-base data that measures critical variables describing the socio-economic and psycho-social status of the English-speaking Black Community. Thus, when it came to exploring the state and vitality of the ESBC, there were and continues to be deficiencies in the publicly available data and knowledge. Being a study about a population that is both a racialized and linguistic minority in Quebec, the Black in Quebec Project attempts to fill some of the gaps in the collection of data, its analysis and storage. It presents an improved understanding regarding the unique situation and challenges facing the ESBC in Quebec.

Drugs & Alcohol : Laws and Regulations - Black Community Resource Centre (BCRC) (2021)

Black in Quebec - Davids, John; Fang, Xiaoyan; Bramble, Shania (2021)

Forum for Youth Insights : Career and Education Orientations for the Post-COVID-19 World - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
The kids are (mostly) alright! That message was made loud and clear during a fascinating discussion when a group of passionate thinkers, educators, students, and speakers got together virtually on October 25, 2020, for Concordia University’s Forum for Youth Insights. An initiative of the Quebec English-Speaking Communities Research Network through its Inter-Level Educational Table, in collaboration with Youth 4 Youth Québec and the Black Community Resource Centre, this year’s forum had a special theme : Career and Education Orientations for the Post-COVID-19 World. In a nutshell, it was an opportunity for students to understand the new realities of the post-COVID-19 experience and how to navigate the sometimes confusing road ahead. Spoiler alert : We’re gonna be alright (but we need to recalibrate slightly).

Forum sur les perspectives jeunesse : orientations professionnelles et éducatives dans le monde post-COVID-19 - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
La jeunesse va (globalement) bien ! Ce message a été exprimé haut et fort lors d’une discussion captivante entre intellectuels, éducateurs, étudiants et conférenciers passionnés, qui s’est tenue virtuellement le 25 octobre 2020 dans le cadre du Forum sur les perspectives jeunesse de l’Université Concordia. L’événement a eu lieu à l’initiative du Réseau de recherche sur les communautés québécoises d’expression anglaise, par l’entremise de sa Table d’éducation interordres et en collaboration avec Youth 4 Youth Québec et le Centre de ressources de la communauté noire. Cette année, le forum avait un thème bien particulier : Orientations professionnelles et éducatives dans le monde post-COVID-19. En résumé, l’occasion a été donnée aux étudiants de saisir les nou- velles réalités de ce « monde d’après » afin qu’ils sachent comment s’engager sur la voie parfois déconcertante qui s’ouvre à eux. Alerte au divulgâcheur : tout va bien aller (mais il nous faudra procéder à quelques ajustements).

Forum for Youth Insights 2020 - Quebec English-speaking Communities Research Network (QUESCREN) (2020)

Call for Papers : The Impact of Black Lives Matter Movement in the Era of COVID-19 Pandemic - International Journal of Community Development & Management Studies (IJCDMS) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Black in Quebec : Systemic Racism in Our History - Davids, John; Fang, Xiaoyan; Galutira, Aileen (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Black in Quebec : Progress Report - Davids, John; Fang, Xiaoyan (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Redefining the Black Experience in Montreal: One Institution at a Time - The Project Woke Interns (Black Community Resource Centre (BCRC), 2020)
Project Woke interns identified and investigated three critical themes affecting the Black community in Montreal. An analysis of societal issues and Canada’s Anti-Racism Strategy Project revealed harmful anti-human rights gaps affecting the Black Community. The findings from several consultations further validated these gaps. A comprehensive list of recommendations is included along with next steps as a continuation to advance Black human rights in Montreal, and elsewhere, along with the support of government and non-government actors.

Evaluation Report - Holley, Paul (Youth for Youth Québec (Y4Y Québec), 2020)
The following evaluation report fulfills a key deliverable of a broader project funded by Canadian Heritage and titled Best Practices in Community Engagement for the English Speaking Youth Population in Quebec, which was implemented by Youth 4 Youth (Y4Y) Quebec from April 1, 2019 to March 31, 2020. The key objective of this project was to boost youth engagement and participation in political and community life in Quebec. Y4Y successfully accomplished this objective by engaging over 1,000 youth through a series of 30 community consultations, 12 focus groups, and a youth survey delivered on-line and in-person with 520 respondents. The focus of this report is on the key findings from the survey, which targeted Englishspeaking youth ages 16 to 30 from across the province and collected quantitative and qualitative information on youth media consumption and community engagement activities. A gender-based analysis of key survey findings was also conducted and is presented in this report along with a set of recommendations for community organizations serving Quebec’s English-speaking youth population.

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)